2019
DOI: 10.1002/da.22909
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences among medical students, house staff, and faculty physicians at high risk for suicide: A HEAR report

Abstract: Background In comparison with the general population, physicians, and physicians‐in‐training are at greater risk for suicide. Although key gender differences in suicide risk factors and behaviors have been identified in the general population, the extent to which these differences apply to physicians and physicians‐in‐training is unclear. Here, we aimed to identify gender differences in risk factors, clinical presentation, and help‐seeking behaviors of medical students, house staff, and physician faculty at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 43 publications
2
12
0
7
Order By: Relevance
“…Our study showed that symptoms of depression and anxiety were significantly more common in girls than in boys. This result is consistent with most previous studies that female sex may be a risk factor for depression and anxiety (51). Among adolescents, the high school students showed significantly higher levels of depression and anxiety symptoms than junior school students, which may be related to more academic pressure, as well as emotional problems linked with physical and mental development.…”
Section: Gender and Age Differencessupporting
confidence: 92%
“…Our study showed that symptoms of depression and anxiety were significantly more common in girls than in boys. This result is consistent with most previous studies that female sex may be a risk factor for depression and anxiety (51). Among adolescents, the high school students showed significantly higher levels of depression and anxiety symptoms than junior school students, which may be related to more academic pressure, as well as emotional problems linked with physical and mental development.…”
Section: Gender and Age Differencessupporting
confidence: 92%
“…Although income gender-inequalities have not been reported in physicians[93,94], some authors suggested that the medical field was mainly dominated by the male gender and reported a poor status integration of women physicians within the profession [7]. It has been shown that female physicians/internships react by imposing themselves an additional pressure to demonstrate their male counterparts that they are as strong, self-sufficient and worthy as them [95].…”
Section: Discussionmentioning
confidence: 99%
“…Depression is a well-established risk factor for suicidal behavior (ideation, attempt and suicide) among medical physicians and nurses ( 37 , 38 ). Our study showed that the severity of self-reported depressive symptoms was associated with suicidal ideation, with the clinical range of depression being the most significant factor.…”
Section: Discussionmentioning
confidence: 99%